Efek Surfaktan pada Stabilitas Nanofluid Nickekl Ferrite - Mahmudi, Riyadi Adnan; Yusuf, Akhmad; Sutjahja, Inge Magdalena (Jurnal Ilmu Fisika, 2025)
Nanofluid stability is a critical factor for the effective application of nanofluids in various fields. One simple and effective method to enhance nanofluid stability is through the addition of surfactants. This study examines the effect of different surfactants on the stability of nickel ferrite (NiFe₂O₄)/water nanofluid. The nanofluids were synthesis using the two-step method, and the surfactants investigated inculded oleic acid, polyethylene glycol 400, tetrabutylammonium bromide, gum arabic, and citric acid. Different concentrations for each surfactant were tested by adjusting the nanoparticles-to-surfactant ratio. The suspension stability was evaluated through visual observation, Zeta potential measurements, and thermal conductivity analysis. The most stable NiFe₂O₄/water nanofluid was achieved using citric acid surfactant, with a nanoparticles-to-surfactant volume ratio of 1:0.25, a Zeta potential value of -35.0 mV and an average thermal conductivity of 0.585 ± 0.007 W/m·K. The results of this study are important for developing nanofluid and magnetic nanofluid systems with optimum conductive heat transfer performance.